Management of The Head of Madrasah Aliyah in Entrepreneurship Development - Gugus Kriswahyudi; Yurnalis Etek; Abshor Marantika; Koderi Koderi; Muhammad Akmansyah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Entrepreneurship in madrasah educational institutions is a necessity that must be carried out to support quality improvement with independent financing. This research has two main objectives: firstly, how the school principal manages to develop entrepreneurship in his institution, and secondly, how the Madrasah principal organizes the organization and implementation of entrepreneurship. This type of research is quantitative, where the data is obtained through informants. The location of this research is two madrasas in Tulang Bawang Regency. The informants for this research came from both madrasahs, namely the head of the madrasah, the deputy head of the madrasah, the head of administration, and the community around the madrasah. Furthermore, the data used is primary data obtained directly from informants through interviews. Test the validity of the data using data triangulation techniques. Meanwhile, data analysis techniques include the degree of trust, transferability, dependability, and confirmability tests. The findings of this research show that the suitable abilities and knowledge of madrasah heads in entrepreneurship influence planning for future educational development. This is demonstrated in the creation of academic curricula. In MAN 1 and MAN 2 Tulang Bawang, all subjects must include entrepreneurship. Apart from that, the placement that will be responsible must be based on the area of skill.